Factors associated with poor treatment outcomes among tuberculosis patients in Kyangwali Refugee Settlement, Uganda, 2016–2017 - Nguna, Joyce; Okethwangu, Denis; Kabwama, Steven Ndugwa; Aliddeki, Dativa Maria; Kironde, Susan Kizito; Birungi, Doreen; Eurien, Daniel; Ario, Alex Riolexus; Lukoye, Deus; Kasozi, Julius; Cegielski, Peter J. (PLOS global public health, 2022)
Communicable diseases, alone or in combination with malnutrition, account for most deaths in complex emergencies including refugee settings. Tuberculosis and HIV/AIDS are increasingly becoming an important cause of morbidity and mortality in refugee settings. We described the treatment outcomes of TB patients and explored factors associated with treatment outcomes among TB patients attending two facilities in Kyangwali Refugee Settlement in Kikuube District, 2016–2017. We abstracted data on laboratory-confirmed patient data from TB registers from 2016 to 2017, in Kikuube Health Centre IV and Rwenyawawa Health Centre II, both located in Kyangwali Refugee Settlement. We abstracted data on socio-demographic variables including age and sex. Other variables were height, weight, final treatment outcomes, demographics, HIV status, TB treatment category, and history of TB. Treatment outcomes were categorized into favorable (including patients who were cured or those who completed treatment) and unfavorable (those in whom treatment failed, those who died, those lost to follow-up, or those not evaluated). We used logistic regression to identify factors associated with unfavorable treatment outcomes. We identified a total of 254 TB patients with a median age of 36 (IQR 26–48) years; 69% (175) were male and 54% (137) were refugees. The median weight was 50.4 kg (range 4–198). Overall, 139 (55%) had favorable outcomes while 115 (45%) had unfavorable outcomes. Refugees formed 53% (71) of those with favorable outcomes and 47% (63) of those with unfavorable outcomes 63(47%). We found that increasing age was statistically associated with unfavorable outcomes, while diagnosis with MDR-TB was associated with decreased odds for unfavorable treatment outcomes. The treatment success rate was lower compared to 85% recommended by WHO. However, the rates are similar to that reported by other studies in Uganda. Innovative approaches to improve treatment success rates with particular focus on persons aged 41–80 years should be devised.